Isolasi Senyawa Antimikroba dari Spon Laut Pseudoceratina Purpurea Carter - Handayani, Dian; Sririta, Martha; Mukhtar, M. Husni (Jurnal Sains dan Teknologi Farmasi, 2010)
An antibacterial compound (HC 2) has been isolated from the n-hexane fraction of marine sponge Pseudoceratina purpurea Carter. Isolation of  HC 2 compound was done by chromatographic method followed by recrystalization. The antimicrobial assay was guided by diffusion method. The compound HC 2 was white needle crystals with melting point 125-127oC. HC 2 compound was tested for an antibacterial activity at concentrations of 5%, 3% and 1% against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus dan Staphylococcus epidermidis bacterials, respectively. Results showed that HC 2 compound had low activity against all bacteria. Identification and characterization of the active compound was confirmed by chemical reactions and infrared spectrum data. HC 2 compound was identified as steroid.